Impact of Sepsis Protocols on Patient outcomes in the ER: A meta-analysis of early sepsis recognition and intervention protocols in emergency settings and their effect on mortality and morbidity - Elshewy, Safwat Mohamed Mohamed (Journal of Neonatal Surgery, 2025)
Background: A significant problem, sepsis is prevalent in a high percentage of hospitalizations that result in death. Aim: To evaluate the impact of Sepsis Protocols on Patient outcomes in the ER. Materials & methods: Our meta-analysis encompasses data from eight studies. The studies involved a total of 701 participants before protocol implementation and 941 participants afterward, reflecting a broad age range and diversity in both sample size and demographic profiles across different settings. Results: The meta-analysis on the effect of sepsis protocol implementation on mortality involved eight studies with a combined total of 1,642 participants. The overall analysis did not show a statistically significant decrease in mortality with the implementation of the sepsis protocol. The pooled analysis demonstrated a statistically significant decrease in the duration of ICU stays by an average of 1.45 days (95% CI: 0.22 to 2.68, Z = 2.31, P = 0.02) following the implementation of the protocol. Conclusion: The sepsis procedure didn’t result in a statistically significant decrease in mortality rates. Heterogeneity was substantial, suggesting conflicting outcomes across studies, and the overall risk ratio was 1.11, showing no protective effect. With a mean difference of 1.45 days, the sepsis protocol's implementation led to a statistically significant decrease in the length of ICU hospitalizations. This result implies that the procedure may successfully lessen the strain on intensive care unit resources